SOCIO-ECONOMIC AND ECOLOGICAL OUTCOMES OF WOODLAND MANAGEMENT IN MUTEMA-MUSIKAVANHU COMMUNAL AREAS IN SAVE VALLEY, SOUTHEASTERN LOWVELD OF ZIMBABWE - C. Mashapa; E. Gandiwa; N. Muboko (Journal of Animal and Plant Sciences, 2019)
This study assessed institutional governance, socio-economic and ecological outcomes of community woodland management in Mutema-Musikavanhu communal areas in Save Valley, southeastern lowveld of Zimbabwe. The study was conducted using household interviews (n = 300), focus group discussions (n = 80) and key informant interviews (n = 20) administered in October to December 2017. The interview questions drew responses on the linkages between local level institutions and communal woodland management for socio-economic outcomes. Using remote sensed imagery of the study area, land use and land cover maps for the period 1990 to 2015 were produced. Woody vegetation structural attributes, abundance and composition were measured to assess the ecological outcomes of communal woodland management. The study findings showed that the local level institutional design influenced socio-economic outcomes that enabled villagers to make up to 12.82% of their Global Annual Income from woodland ecosystem services and goods. Ecological outcomes record showed a decrease of land cover under woodland by over 29%, whereas land under agriculture increased by over 31% during the period 1990 to 2015. The study recorded a J-shaped stage structure of basal area which indicated low recruitment levels and an ageing population of woody vegetation across the study area. Communal woodland management in the study area was likely constrained by weak participation of government forestry extension service and discrepancy in woodland ecosystem benefits sharing among local villagers. Based on the study findings, it was concluded that, provided community woodland resource ownership is secured with equity on access to all members of a society and integrated with active local government regulation, then the likelihood that communities would defer woodland resource use for the future generations is less threatened.
Keywords: communal; ecosystem services; institutions; livelihoods; woodland